FINDING ENTREPRENEURSHIP IN STUDENTS: A CASE STUDY ON THE GRADUATION OF TOURISM IN AZORES UNIVERSITY - Cabral, Joao (European Scientific Journal, ESJ, 2013)
Sometimes the student only needs the teacher fires the spark that ignites a whole new set of ideas and will to do something different, giving their own contribution to the development of new concepts in knowledge. The author in this article shows how a simple discipline of Informatics for Tourism, with sometimes boring concepts to the students, with a scheduled change toward the application in Tourism changed the motivation and helped to implemented team work and development of new ideas in tourism in Azores. This results intend to be a beacon, and an help to improve the techniques of teaching, showing that indeed the student have a lot potential inside and they have the power to develop new ideas. They need only need a small push on the right direction.